Justice Black and the Bill of rights. - Black, Hugo LaFayette, 1886-1971.; Columbia Broadcasting System, inc.; BFA Educational Media (Santa Monica, Calif. : BFA Educational Media, 1969)
Eric Sevareid and Martin Agronsky discuss with Justice Hugo Black possible conflict between constitutional law and morality, freedom of speech, and police powers versus the right of the accused.
DVD
Reproduction from U-Matic.
Telecast as a CBS News special, Dec. 10, 1968.
Producer, Burton Benjamin ; reporters, Eric Sevareid, Martin Agronsky ; photographers, Robert J. Clemens, Robert Hess, John Bessor ; film editor, F. Howard O'Neill.
Also available in VHS.
Keywords: Civil rights -- United States